The effect of schooling on parental integration - Ann-Marie Sommerfeld (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
Exploiting the age-at-enrollment policies in 16 German states as exogenous source of variation, I examine whether the schooling of the oldest child in a migrant household affects parents' integration. My analysis links administrative records on primary school enrollment cutoff dates with micro data from the German Socioeconomic Panel (GSOEP). Using a regression discontinuity design around the school enrollment cutoff and an instrumental variable approach I show that children's schooling improves the integration of parents along several dimensions, such as labor market outcomes, financial worries, and German language skills. Labor market outcomes are most positively affected for mothers. Additional analysis of underlying mechanisms suggests that results are driven by gains in disposable time and exposure to the German language and culture.
Keywords: F22; I24; I26; J16; 330; international migration; assimilation; integration; education; schooling; family; regression discontinuity; instrumental variables